Tindakan Pencegahan Pembakaran Hutan dalam Perspektif ASEAN Community - Kusniati, Retno; Permatasari, Bunga; Rapik, Mohamad (Journal of Political Issues, 2021)
This article aims to elaborate on the values of the ASEAN Community in preventing forest and land fires through the ASEAN Agreement Transboundary Haze Pollution (AATHP), and the Implementation of AATHP in Indonesia. This is because the issue of forest and land fires is one of the main issues in the ASEAN region, and its impact causes cross-border air pollution which results in disruption of diplomatic relations among the ASEAN Member States. Even though ASEAN Member countries have agreed to create an ASEAN Community. Therefore, by applying the normative juridical legal research method, this paper intends to explore several things, namely first; how the values of the ASEAN Community in preventing forest and land fires through the ASEAN Agreement Transboundary Haze Pollution (AATHP), Second, how is the implementation of AATHP in Indonesia. This article finds that the values of the ASEAN Community have been contained in every article regulated in the AATHP for the prevention of forest and land fires that occur in the ASEAN region. Second, Indonesia has ratified the AATHP and made legal products that can reach actors of forest and land burning. This is marked by the passing of the Law on Environmental Protection and Management, the Forestry Law, the Plantation Law, and the Law on Prevention and Eradication of Forest Destruction. Besides, in Jambi Province, Jambi Province has also established Local Regulation Number 2 of 2016 concerning Prevention and Control of Forest and Land Fires.